2022
DOI: 10.3390/biology11060826
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Suggests That Intron Retention Can Affect Quantification of Transposable Elements from RNA-Seq Data

Abstract: Transposable elements (TEs), also known as “jumping genes”, are repetitive sequences with the capability of changing their location within the genome. They are key players in many different biological processes in health and disease. Therefore, a reliable quantification of their expression as transcriptional units is crucial to distinguish between their independent expression and the transcription of their sequences as part of canonical transcripts. TEs quantification faces difficulties of different types, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…As Jonsson and colleagues demonstrated, the abrogated activity of the most important maintenance DNA methyltransferase [ 56 ] erases a fundamental epigenetic repressive layer from the L1 defense mechanisms. Aiming to confirm whether L1 elements were autonomously transcribed [ 57 , 58 ] in this model, we used SQuIRE [ 38 ] to quantify the locus-specific expression of TEs. Our differential expression analysis highlighted that the KO of DNMT1 leads to a strong upregulation of TEs: 3015 TEs result upregulated and 277 downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…As Jonsson and colleagues demonstrated, the abrogated activity of the most important maintenance DNA methyltransferase [ 56 ] erases a fundamental epigenetic repressive layer from the L1 defense mechanisms. Aiming to confirm whether L1 elements were autonomously transcribed [ 57 , 58 ] in this model, we used SQuIRE [ 38 ] to quantify the locus-specific expression of TEs. Our differential expression analysis highlighted that the KO of DNMT1 leads to a strong upregulation of TEs: 3015 TEs result upregulated and 277 downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that incidental signal from L1 sequences nested within retained introns of protein coding genes could interfere with accurate quantification of L1 element expression patterns [56]. We therefore considered the possibility that signals from retroelements nested within retained introns could contribute to the pattern of nuclear enrichment that we observe.…”
Section: Discussionmentioning
confidence: 96%
“…Intron retention is one prominent example of dysfunctional splicing during aging, but the association with age-related transposon expression has not been evaluated. A recent study by Gualandi et al, 2022 using RNA-seq data from the 1000 Genomes project found a strong per sample correlation between intron and transposon expression in the general population. In line with these results, we showed that intron retention may explain a large fraction of transposon reads in aging and senescence datasets ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%